THE INTRODUCTION OF THE DART PROGRAMMING LANGUAGE INTO THE CURRICULUM OF SECONDARY GENERAL EDUCATION - Alimov, Ulugbek Bokhodirovich; Jurakulov, Shakhzod Bakhtiyor ugli (Innovative Development in Educational Activities, 2024)
In modern realities, in the context of digitalization, when the ability to program becomes a second literacy, all spheres of human activity, including the education system, are undergoing changes. These processes have influenced the transformation of some aspects related to schooling. They have led to the emergence of various problematic issues in the field of computer science teaching. In particular, the question concerning the choice of a programming language that would allow the formation of knowledge and skills so necessary for modern schoolchildren.